Disease Burden and Associated Risk Factors of Early-Onset Lung Cancer in China and Worldwide - CAI Lin; ZHU Chenxin; YUAN Jiani; ZHANG Xinglong; FANG Yi; YANG Haiyan; GUO Lanwei (Xiehe Yixue Zazhi)
ObjectiveTo assess the global and Chinese disease burden of early-onset lung cancer(diagnosed in patients aged 15-49 years) and its major risk factors.MethodsBased on the GLOBOCAN 2022 and Global Burden of Disease(GBD) 2021 datasets, we evaluated the disease burden and associated risk factors of early-onset lung cancer globally and in China, stratified by age, sex, geographic location, and human development index(HDI). Key indicators included age-standardized incidence rate(ASIR), age-standardized mortality rate(ASMR), and disability adjusted life years(DALYs) attributable to risk factors.ResultsIn 2022, there were 137 705 new cases and 72 646 deaths from early-onset lung cancer globally, with ASIR and ASMR of 3.43 per 100 000 and 1.82 per 100 000 population, respectively. The disease burden was higher in males than in females(ASIR: 3.72 per 100 000 vs. 3.14 per 100 000; ASMR: 2.31 per 100 000 vs. 1.33 per 100 000). High-HDI regions exhibited the highest ASIR(5.51 per 100 000) and ASMR(2.57 per 100 000), with health inequality analysis revealing a concentration of disease burden in higher-HDI areas. China bore the heaviest burden, accounting for 48.69% of global new cases and 35.77% of deaths. China's ASIR(8.21 per 100 000) and ASMR(3.17 per 100 000) exceeded global averages, with incidence higher in females(8.78 per 100 000 vs. 7.67 per 100 000) but mortality higher in males(4.01 per 100 000 vs. 2.29 per 100 000). Smoking and ambient particulate matter pollution were the leading risk factors globally(DALYs contribution: 42.01% and 15.62%) and in China(DALYs contribution: 46.78% and 20.84%). Globally, household air pollution ranked third, whereas in China, secondhand smoke replaced it as the third leading risk factor, with household air pollution dropping to fifth. Risk factor profiles varied significantly across age groups, with modifiable risks contributing less to disease burden in the 15-24 age group.ConclusionsThe burden of early-onset lung cancer varies markedly by sex, region, and HDI, with China facing a disproportionately high burden. Policymakers should prioritize equitable resource allocation and targeted interventions, particularly in tobacco control and air pollution mitigation, to enhance cancer prevention and control efforts.